NASAFYTOL® supplementation in adults hospitalized with COVID-19 infection: results from an exploratory open-label randomized controlled trial - Gérain, Jean; Uebelhoer, Melanie; Costes, Bérénice; Herman, Julie; Pietri, Sandra; Donneau, Anne-Françoise; Monseur, Justine; Henrotin, Yves (Frontiers in Nutrition, 2023)
Objectives: The effect and safety of Nasafytol®, a food supplement combining curcumin, quercetin, and Vitamin D, on hospitalized COVID-19-positive patients as support to standard of care were to be assessed. Methods: This exploratory, open-label, randomized, controlled trial was carried out among hospitalized adults with COVID-19 infection. Participants were randomly assigned to receive Nasafytol® or Fultium® control. The improvement of the clinical condition and occurrence of (serious) adverse events were evaluated. The study was registered on clincaltrials.gov with the identifier NCT04844658. Results: 25 patients received Nasafytol®, and 24 received Fultium®. Demographic characteristics were well balanced between the groups. On day 14 (or at hospital leave if <14 days), no difference was observed between groups regarding their clinical condition, fever, or the need of oxygen therapy. At day 7, however, 19 participants had been discharged from the hospital in the Nasafytol® arm compared to 10 participants in the Fultium® arm. No participants were transferred to the ICU or died in the Nasafytol® arm, vs. 4 transfers and 1 death in the Fultium® arm. The clinical condition of participants in the Nasafytol® arm had improved, as evidenced by a decrease in the COVID-19 WHO score. Interestingly, five SAEs occurred with Fultium®, while no SAE was observed with Nasafytol®. Conclusions: Supplementation with Nasafytol®, in addition to standard-of-care treatment, led to a faster discharge from the hospital, improved clinical conditions of participants, and a reduced risk of serious outcomes, including transfer to the intensive care unit or death, in patients hospitalized with COVID-19.